A sociological examination of international placement learning by British social work students in children's services in Malaysia - Crabtree, Sara Ashencaen; Parker, Jonathan; Azman, Azlinda; Masud, Faizah (Department of Sociology and the Doctoral School of Sociology of the University of Bucharest., 2014)
This paper discusses research findings into a study of UK student learning on international social work placements in Malaysia in col laboration with two Malaysian universities: Universiti Sains Malaysia and Universiti Malaysia Sarawak. The discussion focuses on those placements taking place in children’s services: residential care and community - based support programmes. The aim of the study was to explore how social work students adapt to unfamiliar learning situations in new cultural contexts with the goal of increasing cultural competence. Data were drawn from formal but anonymised student learning exercises as a non-assessed requirement of this particular placement. Findings indicated a wide range of responses towards social work practice with vulnerable children in the Malaysian context in terms of student constructions of care and abuse. Subject to an analytical schema, the collision or adaptation of otherwise normative professional and personal values are examined in detail